The effects of Cu content on microstructure and mechanical properties of thixoformed A319 aluminium alloys - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Alhawari, Khalid Salim; Mohammed, Mohammed Naser (Trans Tech Publications, 2014)
The effect of copper contents on the microstructure and mechanical properties of A319 aluminium alloy in thixoformed conditions was investigated. The results showed that the addition of 1 wt. % and 2 wt. % copper to A319 alloy reduced the fraction liquid sensitivity and enlarged the working window temperature. Based on the differential scanning calorimetry (DSC) data, the curve of the fraction liquid versus temperature was constructed for each alloy, indicated the temperatures corresponded to the fraction liquid of 30% and 50%. It was found that the working window temperature for A319 alloy of 7 ºC increased to 12 °C when 2 wt. % copper was added, while the sensitivity decreased from 0.027 °C-1 to 0.016 °C-1.The alloy feedstocks produced by cooling slope casting were thixoformed successfully at 40% fraction liquid. The thixoformed A319 alloys attained a hardness level as high as 118.2 ± 2.5 HV when 2 wt. % copper was added.